Making knowledge useful: applying al-Ghazali’s teachings in the Malay world - Moris, Megawati (International Institute of Advanced Islamic Studies Malaysia (IAIS), 2013)
The eighteenth century scholar of Malay–Arab descent Shaykh Abd al-Samad al-Palimbani wrote a seminal Malay-Jawi text entitled Siyar al-Salikin ila Ibadat Rabb al-Alamin, being a translation-cum-commentary on the Mukhtasar Ihya Ulum al-Din of Abu Hamid al-Ghazali. Abd al-Samad’s Siyar exercised a great impact on Malay religious life and thought, by applying al-Ghazali’s teachings to solve the intellectual and religious problems faced by the Malay community during his era. Abd al-Samad discerned two main crises: first, the lack of knowledge among the Malays on the essential teachings of Sufism or tasawwuf; secondly, scholars who suffered from self-delusion and misled their students. He creatively applied encyclopaedic scholarship by providing an extensive bibliography of over one hundred titles of works on Sufism, categorised for each stage of study to ensure qualified access to esoteric knowledge as well as to avoiding misunderstanding of doctrines. Thereby Abd al-Samad made al-Ghazali’s spiritual teachings relevant and useful to the Malays in their attempt to discern truth from falsehood when dealing with competing currents of thought and beliefs prevailing at the time. The problems faced by Malay Muslims three hundred years ago are instructive for us today. Muslims may respond creatively as did Shaykh Abd al-Samad by drawing upon the higher Islamic intellectual tradition for solutions to their present predicament.